Resources on English-Speaking Quebec: A Field Map - O’Donnell, Lorraine; Donovan, Patrick (Minorités linguistiques et société / Linguistic Minorities and Society, 2023)
What characterizes publications and other resources on the scholarly field of English-speaking Quebec as a Canadian official language minority community? To answer this question, we conducted a mapping review of 14,400+ resources listed in Brendan O’Donnell’s online Bibliography on English-Speaking Quebec (quescren.concordia.ca). We found that their publication rate peaked in the 1990s, with a predominant focus on history and the Montreal area. Additionally, these resources primarily cover individuals with origins in the Jewish diaspora, Britain, Ireland, and the United States, addressing topics such as arts, culture, and the media; sociology/anthropology; and politics/government. Relatively few resources focus on English-speaking Quebec as a province-wide collectivity or on federal language legislation. Diversified, but patchy, the English-speaking Quebec field does not appear to be a priority for Quebec’s research institutions.